Acute anterior ischemic optic neuropathy in the course of optic nerve drusen - Gawęcki, Maciej; Doroszkiewicz, Mariusz; Rydzewski, Jacek (Klinika Oczna / Acta Ophthalmologica Polonica, 2007)
Authors present the case of 48 years old male with acute anterior ischemic optic neuropathy (AION) in presence of optic nerve drusen. AION occurred in both eyes, but not at the same time. Diagnosis was made on the basis of laboratory tests, ultrasonographic examination and fluorescein angiography. In the course of treatment improvement of visual acuity was achieved , but concentric constriction of visual field remained. As no effective treatment of non vascular AION was proposed so far, major stress should be put on elimination of its vascular risk factors.